ANALYSIS OF EFFECT OF CUTTING SPEED AND FEED RATE ON CUTTING FORCE DURING THE MACHINING OF 6061 ALUMINUM ALLOYS (International Journal of Engineering Sciences & Management Research, 2018)
This study investigated the effects of the machining parameters, cutting speed, feed rate on main cutting force of 6061 aluminum alloys. The research also examined the effect of cutting parameters, on cutting force by the use of variance analysis (ANOVA). A confidence level of 95% was obtained between all the factors as presented according to the result of variance analysis. The important factor affecting cutting force was cutting speed with 75% significance contribution to the total variation on cutting force. Feed rate with 27.40% significance level has less significant contribution on cutting force. Aluminum Alloy 6061 was machined with tungsten carbide tool using all machining processes with a PATHER 1350 series, lathe machine. The cutting force was measured using cutting tool dynamometer. Two factors were used at three levels (32). The factors are cutting speed and feed rate. The experimental design was done using (Design-Expert7 software) full factorial experimental design. The geometry of the cutting tool was 5°, three different cutting speed 80m/min, 90m/min. 100m/min and feed rate 0.10mm/rev, 0.15mm/rev, 0.20mm/rev according to ISO 3685, and constant depth of cut 1.5 mm were selected as the machining parameters. Build – up edge in the cutting tool and work piece were formed most at cutting speed 80m/min and feed rate of0.10mm/rev.The minimum main cutting force value was determined at 16.84 N at feed rate of 0.1 mm/rev and cutting speed of 80(m/min), while maximum cutting force was determined at 33.59 N at cutting speed of 100 m/min and feed rate of 0.2 mm/rev. According to the test results, increasing the feed rate resulted in an increase in cutting forces. It is suggested that the feed rate must be decreased in order to decrease cutting forces.